Analytical validation of a flow cytometric method for the detection and quantification of canine mast cells in peripheral blood, bone marrow, and lymph node - Iamone, Giulia; Riondato, Fulvio; Hanford, Rachel; Lejeune, Amandine; Kol, Amir (Frontiers in Veterinary Science, 2025)
Mast cell tumors (MCTs) are the most common skin neoplasms in dogs and exhibit highly variable biological behavior. Metastasis primarily affects the lymph nodes, though less frequently, MCTs can infiltrate the spleen, liver, peripheral blood, and bone marrow. Flow cytometry of fine needle aspirate samples represents a non-invasive diagnostic procedure that has shown promise for detecting and quantifying mast cells in primary tumors and lymph nodes. However, analytical validation of this method for clinical use is lacking. This study aimed to evaluate the analytical performance of a flow cytometric panel for quantifying mast cells in peripheral blood, bone marrow, and lymph node aspirates from dogs. Key parameters as the limit of blank (LOB), lower limit of detection (LLoD), lower limit of quantification (LLoQ), intra-assay precision, and accuracy, were evaluated. The method demonstrated high precision across a wide range of mast cell concentrations, with analytical coefficient of variation (CVA) of less than 10% for all sample types. It also showed good accuracy with minimal proportional bias observed in lymph node samples, particularly at higher mast cell concentrations. The LLoQ was 0.1% for all sample types. Flow cytometry provided reliable results highlighting its potential as a clinical tool for diagnosing and staging MCTs. These findings support the clinical applicability of flow cytometry as a minimally invasive, highly accurate method for assessing mast cell infiltration in peripheral blood, bone marrow, and lymph nodes, offering an alternative to traditional microscopic examination. This validation establishes a foundation for future studies on the prognostic implications of mast cell infiltration in MCT progression.